Towards secure smart cities: design and implementation of smart home digital communication system - Nael Al-Shareefi; Sura Adil Abbas; Mohanad S. Alkhazraji; Ammar AbdRaba Sakran (Institute of Advanced Engineering and Science, 2021)
Home and building security are major concern in our daily life and digital smart door lock (DSDL) have become an essential part of these systems. In this paper, a secure DSDL which can grant access to home with a fingerprint is designed and implemented. An Arduino Nano microcontroller board, finger print sensor and servo motor have been utilized for lock/unlock door based on finger print. The DSDL is an automatic authenticate and validate the user for secure access. The implemented system aims to develop a cost−effective DSDL based on low−cost components compared to the systems already on the domestic market. The−ease of−use and cost−effectiveness makes the DSDL a strong competitor to the digital security system on the domestic market and outperforms it and suitable for security–based home automation systems.